The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/jof7121072
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Clinical and Laboratory Patterns of Pneumocystis jirovecii Pneumonia in Renal Transplant Recipients

Abstract: Late post-transplant Pneumocystis jirovecii pneumonia (PcP) has been reported in many renal transplant recipients (RTRs) centers using universal prophylaxis. Specific features of PcP compared to other respiratory infections in the same population are not well reported. We analyzed clinical, laboratory, administrative and radiological data of all confirmed PcP cases between January 2009 and December 2014. To identify factors specifically associated with PcP, we compared clinical and laboratory data of RTRs with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…The additional 73 studies were evaluated furtherly through a full‐text review. Ultimately, a total of 27 retrospective studies published between 1995 and 2022 were included in the meta‐analysis 6,8,14–38 . Among them, 15 studies are from Europe, 6 are from Asia, 5 are from the Americas, and 1 is from Oceania.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The additional 73 studies were evaluated furtherly through a full‐text review. Ultimately, a total of 27 retrospective studies published between 1995 and 2022 were included in the meta‐analysis 6,8,14–38 . Among them, 15 studies are from Europe, 6 are from Asia, 5 are from the Americas, and 1 is from Oceania.…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, it was found that eight factors are associated with PJP occurrence: age at transplantation, ABO‐incompatibility, acute rejection, CMV infection, BK viremia, anti‐PJP prophylaxis, eGFR and lymphocyte count. Some studies have investigated risk factors for PJP before, such as age, CMV infection, transplant rejection episodes, dialysis time and Tacrolimus dose 7,9,14–38 . However, these conclusions differ, which could be attributed to the fact that people are from different regions of the world.…”
Section: Discussionmentioning
confidence: 99%